2013
DOI: 10.1532/hsf98.20121073
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Type of Aortic Valve Prosthesis on Coronary Blood Flow Velocity

Abstract: The coronary flow velocity profile in the LAD was significantly influenced by the type of aortic valve prosthesis used. The differences in the LAD velocity profile probably reflect differences in valve design and the systolic transvalvular flow pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…These are the total number of patients in the studies and not the patients at risk at the time of follow-up. In five studies (n ¼ 441), measurement with transthoracic echocardiography showed left ventricular (LV) mass decreased 19% to 32% up to 2 years of follow-up compared with preoperative measurements (p < 0.05) [13][14][15][16]18]. In six studies (n ¼ 745), LV end-diastolic diameters decreased 3% to 10% and LV end-systolic diameters decreased 6% to 12% during 1 to 2 years of follow-up [15,16,[18][19][20][21].…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…These are the total number of patients in the studies and not the patients at risk at the time of follow-up. In five studies (n ¼ 441), measurement with transthoracic echocardiography showed left ventricular (LV) mass decreased 19% to 32% up to 2 years of follow-up compared with preoperative measurements (p < 0.05) [13][14][15][16]18]. In six studies (n ¼ 745), LV end-diastolic diameters decreased 3% to 10% and LV end-systolic diameters decreased 6% to 12% during 1 to 2 years of follow-up [15,16,[18][19][20][21].…”
Section: Clinical Outcomesmentioning
confidence: 99%